2012
DOI: 10.5562/cca1972
|View full text |Cite
|
Sign up to set email alerts
|

Highly Exfoliated Graphite Fluoride as a Precursor for Graphene Fluoride Dispersions and Films

Abstract: Abstract. We synthesized highly exfoliated graphite fluoride of approximate composition C 2 F by treating highly exfoliated graphite with ClF 3 . The formed material was found to be dispersible in solvents giving 1 to 5 layered fluorinated graphene. Dispersions successfully formed in polar organic solvents capable of establishing hydrogen bonds. The highest stability is achieved in branched alcohols such as tert-butanol. The dispersions may be further processed into thin films by vacuum filtration technique. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Graphene (G) was obtained by liquid-phase exfoliation of graphite in dimethylformamide (DMF) [ 33 , 34 ]. The so-prepared G samples consisted of 2–5 layers [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…Graphene (G) was obtained by liquid-phase exfoliation of graphite in dimethylformamide (DMF) [ 33 , 34 ]. The so-prepared G samples consisted of 2–5 layers [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, graphene as a carbon material has high electrical conductivity, which hinders its application in scenarios that demand high insulation and low dielectric loss [ 27 ]. In this context, fluorinated graphene (F-graphene), a graphene derivative, has been given great expectations for its excellent properties such as high thermal conductivity, wide band gap (3.0–4.2 eV), low electrical conductivity (10 −11 S/cm) and high stability, which is mainly due to the invasion of fluorine that transforms the structure of C-C bonds from sp 2 to sp 3 [ 28 , 29 , 30 , 31 , 32 , 33 ]. For example, Yang et al fabricated polymer nanodielectrics employing F-graphene and polyvinylidene fluoride (PVDF) and found that adding 0.2 wt.% of F-graphene could enhance the breakdown strength ( E b ) by 39.4% and simultaneously reduce the dielectric loss [ 34 ].…”
Section: Introductionmentioning
confidence: 99%